United States Foreign Policy in Addressing Iran's Nuclear Program 2021-2024 - I Wayan Aditya Harikesa; Anggun Dwi Panorama; Fillah Tri Dharmawan Maskur Putra (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study analyzes the United States’ foreign policy toward Iran’s nuclear program during 2021–2024. In 2022, President Joe Biden expressed the intention to resume dialogue with Iran; however, this effort was rejected by 48 Republican senators who insisted on continuing the Maximum Pressure policy initiated during the Trump administration. Using a qualitative approach and literature study, this research examines the interplay between identity, domestic politics, economic strength, and military capacity in shaping U.S. foreign policy. The findings reveal that the construction of U.S. national identity, reinforced through social and political interactions, significantly influences the formulation of foreign policy. These factors led decision makers, particularly the President, to maintain the Maximum Pressure strategy as the main approach in addressing Iran’s nuclear ambitions during the 2021–2024 period.